Analysis of the Quality of Smoked Skipjack Fish with Coconut Shell Curing Material During Storage at Room Temperature - Azis Husen; Ibnu Wahab Laitupa (Agrikan: Jurnal Agribisnis Perikanan, 2020)
Ternate has abundant skipjack pelagic fish fishery resources and it becomesas a process smoked fish which is consumed by all people from lower, middle to upper level. This study aims to determine the quality of smoked skipjack fish by using coconut shells. Organoleptic observations include appearance, color, aroma, taste, texture, appearance. The methods used in this research are descriptive and quantitative methods. With organoleptic and microbiological test parameters (Total Plate Figures). The samples used for analysis were 12 tails for 8 organoleptic testing and 4 for ALT testing. The organoleptic test results on smoked skipjack tuna on the color, taste, aroma, naming, and texture of the five analyzes were still acceptable to the 27 panalis of smoked skipjack tuna produced on the first, second and third day after the third day of meat the skipjack tuna that is stored has deteriorated quality and is contaminated by bacterial fungi, so the fourth, fifth, and sixth day of coconut shell smoked cakalng fish can no longer be consumed. The results of the ALT microbiological test for smoked skipjack tuna obtained the lowest value was 33.602, the second with a value of 36.006 and the third 37.505 from the test results the smallest bacteria with a value of 33.602.